Expression of cancer–testis antigens in esophageal cancer and their progress in immunotherapy - Yujie Zhang; Yuxin Zhang; Li Zhang (2019)
Esophageal cancer is a common disease in China with low survival rate due to no obvious early symptoms and lack of effective screening strategies. Traditional treatments usually do not produce desirable results in patients with advanced esophageal cancer, so immunotherapy which relies on tumor-related antigens is needed to combat low survival rates effectively. Cancer–testis antigens (CTA), a large family of tumor-related antigens, have a strong in vivo immunogenicity and tumor-restricted expressing patterns in normal adult tissues. These two characteristics are ideal features of anticancer immunotherapy targets and, therefore, promoted the development of some studies of CTA-based therapy. To provide ideas for the role of the cancer–testis antigens MAGE-A, NY-ESO-1, LAGE-1, and TTK in esophageal cancer, we summarized their expression, prognostic value, and development in immunotherapy. The relevant literature from PubMed is reviewed in this study. In esophageal cancer, although the relationship between expression of MAGE-A, NY-ESO-1, LAGE-1, and TTK and prognosis value is still in a controversial situation, MAGE-A, NY-ESO-1, LAGE-1, and TTK are highly expressed and can induce specific CTL cells to produce particular killing effect on tumor cells, and some clinical trials have demonstrated that immunotherapy for esophageal cancer patients is effective and safe, which provides a new therapeutic strategy for the treatment of esophageal cancer in the future. In this review, we summarize expression and prognostic value of MAGE-A, NY-ESO-1, LAGE-1, and TTK in esophageal cancer and point out recent advances in immunotherapy about them.